Psychosocial challenges affecting the quality of life in adults with epilepsy and their carers in Africa: A review of published evidence between 1994 and 2014 - Mpoe J. Keikelame; Tamzyn Suliaman; Marleen Hendriksz; Leslie Swartz (AOSIS, 2017)
Background: Little attention has been paid to the psychosocial challenges of adult patients with epilepsy and their carers in Africa in published studies conducted between 1994 and 2014 - yet these psychosocial challenges have been reported to have a major impact on the quality of life (QOL) of people living with the illness and those who care for them. Aim: This review aimed to examine the literature on published studies conducted in Africa between 1994 and 2014 that examined psychosocial challenges of adult people with epilepsy and their carers. The aim was to examine the kind of psychosocial challenges from published evidence and to identify gaps in current knowledge. Methods: MEDLINE, PubMed, ERIC, Web of Science, Scopus, Cochrane Library, Africa Wide, PsycINFO, EMBASE, PASCAL, SABINET and Google Scholar databases and hand searches of Epilepsy & Behavior, Epilepsia, South African Medical Journal, African Journal of Disability, African Journal of Primary Health Care and Family Medicine were reviewed. Results: Very few studies in Africa have examined psychosocial challenges affecting the adult patients with epilepsy and their carers. This review reported the existence of evidence of such challenges and the insights into the psychosocial and economic factors that underpin them. There is evidence that where these have been addressed, there were valuable insights on the types of psychosocial, socio-cultural and socio-economic challenges. Collaborative empowering interventions are needed to enable the attainment of good QOL for those affected. Conclusion: Research on psychosocial challenges of adult patients with epilepsy and their carers from different sectors of healthcare to inform the design of appropriate models is needed.